Saberes teóricos e práticos necessários ao ensino de Matemática destinado a pessoas surdas - Oliveira, Camila Rezende (2021)
This research aimed to study master's dissertations and doctoral theses produced between 2010 and 2020 that dealt with the theme of Deafness and Mathematics in Elementary School, and to identify and analyze what teachers need to know to effectively develop the teaching of Mathematics to deaf people. Deaf subjects are those who understand and interact with the world through visual experiences, with sign language, Libras, being one of the most important of these experiences. The work started from the following investigative question: What is the knowledge that elementary school teachers need to know to effectively develop the teaching of Mathematics for deaf people? The research was theoretically supported by authors in the area of Deafness, Mathematics Education and Inclusion, including: Skliar (2001), Fiorentini and Lorenzato (2006), Mantoan (2005) in addition to recent research carried out in the area of Inclusive Mathematics Education. The methodological option was the Meta-analysis, which sought dissertations and theses between 2010 and 2020 that focused on Elementary School Mathematics teachers, Specialized Educational Service teachers - AEE and Libras Interpreters - ILS in the theses database and dissertations from Capes and at the Digital Library of Theses and Dissertations – BDTD. The keywords used were the following in the search: Deafness and Mathematics; Mathematics and Deafness Teachers; Deaf and Mathematics; Early Years and Deafness; Hearing and Mathematical Impairment; AEE and Deafness Teachers; Final Years and Deafness; Elementary School and Deafness. For data analysis, the abstract, theoretical chapters and sometimes the results and final considerations of theses and dissertations were read. The results found in this research were based on the following knowledge in the academic works analyzed: knowledge of inclusion, knowledge of Libras; knowledge of Mathematics training; knowledge of culture and deaf studies; knowledge of visual pedagogy in Mathematics Teaching; knowledge of mathematical content; knowledge of conceptions and beliefs about Mathematics; knowledge of mathematical concepts and learning. Still under this focus, most of the works evaluated had as main concern the acquisition of Brazilian Sign Language by both deaf and hearing students. This concern also permeates professionals who deal specifically with this student target audience of Inclusive Education. This fact demonstrates the eminent need for more fruitful contributions in order to remedy the scientific gap that still exists in the knowledge that teachers need to obtain to improve the inclusion of deaf students present in Basic Education.